Digital Marketing Risk Assessment Based on ISO 31000: Empirical Evidence from the Indonesian OTA Sector - Indra Gunawan; Rudy Sondang Sinaga; Alfonso Harrison (Politeknik Siber Cerdika Internasional, 2026)
Background: Online marketing campaigns are marketing strategies that utilize digital technology to promote products or services through the internet. Objective: The goal of these campaigns is to increase brand awareness, engagement, and sales in a more effective and efficient manner. Methods: Online marketing campaigns involve various methods, including search engine advertising, social media marketing, email marketing, and content marketing. Results: In Indonesia, the widespread adoption of internet technology and the rapid development of digital platforms provide significant opportunities for companies to reach broader and more diverse markets. Online marketing campaigns enable companies to gain deeper insights into target markets, measure return on investment (ROI) more accurately, and strengthen their competitive advantage in an increasingly competitive environment. A structured approach and appropriate strategies in online marketing campaigns assist companies in optimizing the utilization of digital technologies to achieve their marketing objectives. Conclusions: Thus, online marketing campaigns have become essential tools for companies in responding to technological advancements and continuously evolving consumer needs.